Implementasi Etika Bisnis Islam dan Dampaknya Terhadap Loyalitas Pelanggan Pada Unit Usaha Aqiqoh Nurul Hayat Medan - Wardana, Ilham Tri; Ramadhani, Sri (Universitas Labuhanbatu, 2022)
The purpose of this study is to determine how the implementation of Islamic Business Ethics and its impact on customer loyalty in the foundation Aqiqah Nurul Hayat Medan. This study uses qualitative methods. The purpose of the use of qualitative methods is to understand the phenomenon of what is experienced by the subject of research, in the subject under study there are several types of data, namely internal and external, in the internal subject, namely employees who are in the division of the business Unit in charge of carrying out Marketing Operations at the foundation Aqiqah Nurul Hayat Medan, while the external data subject is the customer of the foundation Aqiqah Nurul Hayat Medan. Another external research subject is a customer who has subscribed or purchased Aqiqah services at the Nurul Hayat Medan Aqiqah Foundation to provide information about how the implementation of Islamic Business Ethics at the Nurul Hayat Medan Aqiqah Foundation. Data collection in this study using interview techniques to find out and get the desired data continued with documentation techniques and direct observation. The results of this study show that the implementation of Islamic Business Ethics has a significant impact on increasing customer loyalty in the Aqiqah Nurul Hayat Medan Foundation, such as customer satisfaction through honest employee performance and attention to the halality of the products sold.